1999
DOI: 10.1021/js9803555
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal and thermal characteristics of concentrated dispersions of polymethacrylate-based latices for aqueous enteric coating

Abstract: We have used rheological and thermal methods to study the colloidal characteristics of a widely used technical latex. The dispersions of poly(methacrylic acid-ethyl acrylate) (Eudragit L100-55) were found to be stabilized by a combination of electrostatic and steric mechanisms termed as electrosteric stabilization. The electrosteric stabilization is considered to arise in part from dissolved polymer chains with charged carboxylic groups extending out into the continuous phase. The presence of dissolved polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, the addition of sodium chloride or potassium chloride did not cause any flocculation, suggesting absence of any electrostatic forces between the particles. These experiments explain the stability behind the polymeric particles of pseudolatex 13. The key issue in pseudolatex dispersion is long‐term stability.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…However, the addition of sodium chloride or potassium chloride did not cause any flocculation, suggesting absence of any electrostatic forces between the particles. These experiments explain the stability behind the polymeric particles of pseudolatex 13. The key issue in pseudolatex dispersion is long‐term stability.…”
Section: Resultsmentioning
confidence: 75%
“…The Dougherty‐Kreiger equation for a hard sphere system is given by η r = (1− Φ eff /Φ eff,m ) −[η] Φeff,m , where, Φ eff is the effective volume fraction, Φ eff,m is the maximum theoretical packing fraction corresponding to a hexagonally packed sphere structure (loose packing, coordination number 8)13 and [η] is the intrinsic viscosity. From all other values, Φ eff can be calculated and an estimate of Δ can be figured to fit the experimental points (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Steric stabilization (due to the presence of the nonionic surfactant polysorbate 80) may also play a role because of the high stability of Eudragit ® L 30 D‐55 to the dyes at pH 5.2. Paulsson and Singh12 have reported that an electrosteric stabilization mechanism from the dissolved polymer chains is also present in this latex. One reason why Eudragit ® L 30 D‐55 exhibits higher critical coagulation concentrations than Eudragit ® RS 30 D is because, like the dyes, it is negatively charged.…”
Section: Resultsmentioning
confidence: 79%
“…According to Schuman et al (2004b,c), latex films do not contain crystalline regions, i.e., they are totally amorphous. Depending on latex composition and RH of storage, T g can vary widely, typically from 30 to 130°C (Paulsson and Singh, 1999;Xu et al, 2005). For styrene-acrylate lattices, Nestorson et al (2007) determined a T g value in the range of 2-5°C.…”
Section: Packaging Properties Influencing Aroma Compound Transfermentioning
confidence: 99%